Procoagulant extracellular vesicles alter trophoblast differentiation in mice by a thrombo-inflammatory mechanism - Markmeyer, Paulina; Lochmann, Franziska; Singh, Kunal Kumar; Gupta, Anubhuti; Younis, Ruaa; Shahzad, Khurrum; Biemann, Ronald; Hübner, Hanna; Rübner, Matthias; Isermann, Berend; Kohli, Shrey (International Journal of Molecular Sciences, 2021)
Procoagulant extracellular vesicles (EV) and platelet activation have been associated with gestational vascular complications. EV-induced platelet-mediated placental inflammasome activation has been shown to cause preeclampsia-like symptoms in mice. However, the effect of EV-me-diated placental thrombo-inflammation on trophoblast differentiation remains unknown. Here, we identify that the EV-induced thrombo-inflammatory pathway modulates trophoblast morphology and differentiation. EVs and platelets reduce syncytiotrophoblast differentiation while increasing giant trophoblast and spongiotrophoblast including the glycogen-rich cells. These effects are plate-let-dependent and mediated by the NLRP3 inflammasome. In humans, inflammasome activation was negatively correlated with trophoblast differentiation marker GCM1 and positively correlated with blood pressure. These data identify a crucial role of EV-induced placental thrombo-inflamma-tion on altering trophoblast differentiation and suggest platelet activation or inflammasome activation as a therapeutic target in order to achieve successful placentation.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Extracellular vesicles; Inflammasome; thrombo-inflammation; Trophoblast differentiation